PENGARUH RASIO CAR, NPL, LDR, BOPO, DAN NIM TERHADAP KINERJA BANK UMUM DI INDONESIA - Dwi Priyanto Agung Raharjo; Bambang Setiaji; Syamsudin Syamsudin (Jurnal Manajemen Dayasaing, 2014)
This research is performed on order to test the inﬂuence of the variable Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Loan to Deposit Ratio (LDR), BOPO (Operating Expenses / Operating Income), and Net Interest Margin (NIM), to return on Asset (ROA). The sample used in the study were 120 bank in Indonesia in 2010 and 2011. The data analysis technique used is multiple linear regression, t-statistic and F-statistics test with a signiﬁcance level of 5%. During research period show as variable and data research was normal distributed. Based on test, multicolinearity, heterosscedasticity and autocorrelation classic assumption deviation has no founded, this indicate that the available data has fulﬁll the condition to use multi linear regression model. This result of research show that variable CAR, NIM, and LDR positive signiﬁcant inﬂuence toward ROA. Variable NPL and BOPO negative signiﬁcant inﬂuence toward ROA. Prediction capability from these seven variable toward ROA is 78,7 % where the balance 21,3% is affected to other factor which was not to be entered to research model.